INNOVATIVE STRATEGIES IN LEARNING DESIGN BASED ON STRENGTHENING LEADERSHIP SKILLS - Farisi, Yudik Al-; Jazilurrahman, Jazilurrahman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to describe Innovative Strategies in Learning Design Based on Leadership Skill Enhancement. This objective is grounded in the developments of the globalization era and Industry 4.0, where the challenges faced by leaders and educators in educational institutions are becoming increasingly complex. Changes in the field of education, technological advancements, student diversity, and rising societal demands require school leaders to adapt and respond to changes rapidly. Research on educational leadership in institutions is becoming increasingly relevant and urgent to explore. To gather data for this study, a qualitative approach with a case study design was employed. The research setting was located at MA Nurul Jadid Paiton, Probolinggo, and the study was conducted from October 10 to December 10, 2024. Data collection techniques utilized snowball sampling, with primary and secondary sources as the data basis. Data were collected through participant observation, in-depth interviews, and documentation. The data analysis technique followed the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results of this study indicate that Innovative Strategies in Learning Design Based on Leadership Skill Enhancement at MA Nurul Jadid Paiton, Probolinggo, include: Competency Standards Development,Training and Development, Mentorship and Coaching, and Monitoring and Evaluation. The design of leadership skills in learning plays a crucial role in creating an effective learning environment and empowering leaders who can effectively manage the learning process.